Acute Effects of an Energy Drink on Myocardial Function Assessed by Conventional Echo-Doppler Analysis and by Speckle Tracking Echocardiography on Young Healthy Subjects. (10th November 2013) - Menci, Daniele; Righini, Francesca Maria; Cameli, Matteo; Lisi, Matteo; Benincasa, Susanna; Focardi, Marta; Mondillo, Sergio
Abstract : Purpose . Previous studies have underlined the effects of the energy drinks containing caffeine end taurine on the cardiovascular system. The aim of this study was to determine acute changes on echocardiographic parameters assessed by conventional echo-Doppler analysis and by speckle tracking echocardiography after the consumption of an energy drink in a young healthy population. Methods . measurement of blood pressure, electrocardiographic, and echocardiographic examination were performed on 35 healthy subjects (mean age 25 ± 2 years, 16 men), at baseline and one hour after the consumption of a body surface area indexed amount of an energy drink (168 mL/m 2 ) containing caffeine (0.03%) and taurine (0.4%). Results . The analysis of left ventricular function showed a significant increase of mean relative values of MAPSE (+11%; P < 0.001 ), global longitudinal strain (+10%, P = 0.004 ), and left ventricular twisting (+22%, P < 0.0001 ) in respect to baseline. Also, right ventricular function parameters appeared significantly increased after energy drink consumption, as TAPSE (+15%, P < 0.0001 ), global, and free wall right ventricular longitudinal strain (+8%, P = 0.001 ; +5%, P = 0.1, resp.). Conclusion . In conclusion, the consumption of the ED in our population showed a significant increase of right and left ventricular myocardial function, suggesting a possible positive inotropic effect related to the substances contained therein.